Academic Senate Minutes 2004-03-18 - Academic Senate:::::::::
Approval of Agenda. Approval of Minutes of 8/23/12. Correspondence report. Chair Report. Dean Merickel Report to the Senate. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. APC report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate agenda approved.